2018
DOI: 10.1111/bjet.12655
|View full text |Cite
|
Sign up to set email alerts
|

Young children, digital media and smart toys: How perceptions shape adoption and domestication

Abstract: Contemporary homes are filled with digital technologies, and children are exposed to them almost since birth, initiating their first digital experiences at very early ages (Chaudron et al., , Young children (0–8)). This trend is expected to become stronger, as our future has been envisioned around the concept of the IoT (Internet of Things), and the first smart toys are arriving at the homes of digitally savvy families. This study focuses on the digital practices of young children, looking particularly at smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 22 publications
1
40
0
3
Order By: Relevance
“…All this leads us to conclude that knowing the resources does not imply using them regularly according to the professional-didactic potential that they offer (evaluative, communicative, training, planning, etc.). In agreement with the background presented in the introduction and in line with the studies that have addressed the training of teachers in ICT, we must advocate for the improvement of the training of ECE teachers in its three dimensions: disciplinary, pedagogical and technological (Brito et al, 2018;Cabero, 2014;Prendes & Gutierrez, 2013;Valverde et al, 2010). Based on this three-dimensional model of ICT integration, our results, in a way, reflect that training in only one of these (technological) dimensions does not guarantee its integration into the classroom from a didactic-disciplinary perspective.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…All this leads us to conclude that knowing the resources does not imply using them regularly according to the professional-didactic potential that they offer (evaluative, communicative, training, planning, etc.). In agreement with the background presented in the introduction and in line with the studies that have addressed the training of teachers in ICT, we must advocate for the improvement of the training of ECE teachers in its three dimensions: disciplinary, pedagogical and technological (Brito et al, 2018;Cabero, 2014;Prendes & Gutierrez, 2013;Valverde et al, 2010). Based on this three-dimensional model of ICT integration, our results, in a way, reflect that training in only one of these (technological) dimensions does not guarantee its integration into the classroom from a didactic-disciplinary perspective.…”
Section: Discussionsupporting
confidence: 60%
“…This would represent one of the first order barriers, according to the review by Dagnino et al (2018), about the difficulties that teachers present in the use of technological resources. These findings may be related to the hypothesis proposed by Brito, Dias and Oliveira (2018), according to which, behind these difficulties, there would be a lack of knowledge by ECE teachers for the creation of learning processes that include technology, knowledge that they should have acquired during their initial training. On the other hand, regardless of training, the limited use of ICT could be related to the beliefs of ECE teachers, as noted by Wood et al (2008), that consider them inappropriate while teaching 4 years old children or younger.…”
Section: Discussionmentioning
confidence: 72%
“…Digitods are the first cohort to grow up entirely after the launch of smartphones to the popular market, with most having grown up in households with access to portable touch-screen devices with enhanced computing power and mobility (Livingstone and Helsper 2007;Kucirnova and Sakr 2015). The new cohort of 'digitods' have parents who tend to be experienced digital users themselves and who often adopt 'new' digital parental mediation strategies to promote children's safe media use and digital literacy (Bennett et al 2008;Brito et al 2018). Yet, younger children are increasingly exposed to a multitude of digital technologies at a very early age (Mascheroni and Olafsson 2016), which may lead to potential well-being problems associated with excessive screen-time or nondevelopmentally appropriate media use.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they should be offered alternative mediums for self-expression for ensuring rich data. The use of visual methods and materials, such as drawing and pictures, is typical in contemporary childhood research (Lipponen, Rajala, Hilppö, & Paananen, 2016), and this has proven to provide rich data for exploring young children's meaning making around digital technologies (Brito et al, 2018;Mertala, 2016Mertala, , 2019Robertson et al, 2017). In this study, visual materials were used as supports for verbal narration (pictures shown to children) and forms of visual narration (drawing task).…”
Section: Participants Research Context and Data Collectionmentioning
confidence: 99%
“…IoT toys may not be everyday playthings for the vast majority of children today (Brito, Dias, & Oliveira, 2018), they most likely will be in a few years. This qualitative study contributes to filling this knowledge gap by exploring 3-to 6-year-old Finnish children's perceptions of ubicomp and IoT via picture-enhanced interviews and a design task.…”
Section: Introductionmentioning
confidence: 99%